Ruang Digital sebagai Arena Konstruksi Identitas Sosial Generasi Z : Studi Fenomenologi pada Komunitas Gamer - Agung Putra Mulyana; Muhammad Irfan; Khoirul Majid (Institut Nalanda, 2026)
The development of digital technology has transformed patterns of social interaction, particularly among Generation Z, who grow and develop within a virtual communication ecosystem. The presence of digital spaces enables the formation of various online communities that function as platforms for social interaction as well as the construction of self-identity. This study aims to understand the process of forming Generation Z’s social identity through interpersonal communication within gamer communities in digital spaces. The research employed a qualitative approach with a phenomenological design to explore individuals’ subjective experiences in their daily digital interactions. Data were collected through observation, in-depth interviews, and documentation involving members of the gamer community at SMK Bina Insan Mandiri. The results show that interpersonal communication within gamer communities occurs intensively and reflects characteristics such as openness, empathy, supportiveness, positive attitudes, and equality among members. These interactions not only strengthen social relationships but also shape social identity through the use of distinctive language, shared experiences, repetitive communication patterns, and a sense of belonging to the community. These findings confirm that digital spaces function as alternative social arenas for Generation Z in building self-identity in a more dynamic way.